Didactic Principles Aimed at the Development of Electronic Publications - Shaynazarov Ravshan Mamayusubovich (Genius Journals, 2022)
This article presents didactic principles focused on the development of electronic publications. In addition, theoretical analyzes are presented on the development of students ' preparations for graphically visualizing using computer technology.
Keywords: Hypertext; didactic principle; electronic textbook; visualization graphic visualization method